Answer
The solutions to the system of equations are:
1. \( \left( \frac{7 + \sqrt{61}}{6}, \frac{-7 + 5\sqrt{61}}{6} \right) \)
2. \( \left( \frac{7 - \sqrt{61}}{6}, \frac{-7 - 5\sqrt{61}}{6} \right) \)
Solution
Solve the system of equations by following steps:
- step0: Solve using the substitution method:
\(\left\{ \begin{array}{l}y=3x^{2}-2x-8\\y=5x-7\end{array}\right.\)
- step1: Substitute the value of \(y:\)
\(3x^{2}-2x-8=5x-7\)
- step2: Move the expression to the left side:
\(3x^{2}-2x-8-\left(5x-7\right)=0\)
- step3: Subtract the terms:
\(3x^{2}-7x-1=0\)
- step4: Solve using the quadratic formula:
\(x=\frac{7\pm \sqrt{\left(-7\right)^{2}-4\times 3\left(-1\right)}}{2\times 3}\)
- step5: Simplify the expression:
\(x=\frac{7\pm \sqrt{\left(-7\right)^{2}-4\times 3\left(-1\right)}}{6}\)
- step6: Simplify the expression:
\(x=\frac{7\pm \sqrt{61}}{6}\)
- step7: Separate into possible cases:
\(\begin{align}&x=\frac{7+\sqrt{61}}{6}\\&x=\frac{7-\sqrt{61}}{6}\end{align}\)
- step8: Evaluate the logic:
\(x=\frac{7+\sqrt{61}}{6}\cup x=\frac{7-\sqrt{61}}{6}\)
- step9: Rearrange the terms:
\(\left\{ \begin{array}{l}x=\frac{7+\sqrt{61}}{6}\\y=3x^{2}-2x-8\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{7-\sqrt{61}}{6}\\y=3x^{2}-2x-8\end{array}\right.\)
- step10: Calculate:
\(\left\{ \begin{array}{l}x=\frac{7+\sqrt{61}}{6}\\y=\frac{-7+5\sqrt{61}}{6}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{7-\sqrt{61}}{6}\\y=-\frac{7+5\sqrt{61}}{6}\end{array}\right.\)
- step11: Check the solution:
\(\left\{ \begin{array}{l}x=\frac{7+\sqrt{61}}{6}\\y=\frac{-7+5\sqrt{61}}{6}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{7-\sqrt{61}}{6}\\y=-\frac{7+5\sqrt{61}}{6}\end{array}\right.\)
- step12: Rewrite:
\(\left(x,y\right) = \left(\frac{7+\sqrt{61}}{6},\frac{-7+5\sqrt{61}}{6}\right)\cup \left(x,y\right) = \left(\frac{7-\sqrt{61}}{6},-\frac{7+5\sqrt{61}}{6}\right)\)
To solve the system of equations given by:
1. \( y = 3x^2 - 2x - 8 \)
2. \( y = 5x - 7 \)
we can set the two equations equal to each other since they both equal \( y \):
\[
3x^2 - 2x - 8 = 5x - 7
\]
Now, let's rearrange this equation to bring all terms to one side:
\[
3x^2 - 2x - 5x - 8 + 7 = 0
\]
This simplifies to:
\[
3x^2 - 7x - 1 = 0
\]
Next, we can use the quadratic formula to find the values of \( x \):
\[
x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
where \( a = 3 \), \( b = -7 \), and \( c = -1 \).
Calculating the discriminant:
\[
b^2 - 4ac = (-7)^2 - 4 \cdot 3 \cdot (-1) = 49 + 12 = 61
\]
Now substituting back into the quadratic formula:
\[
x = \frac{7 \pm \sqrt{61}}{6}
\]
This gives us two possible values for \( x \):
1. \( x_1 = \frac{7 + \sqrt{61}}{6} \)
2. \( x_2 = \frac{7 - \sqrt{61}}{6} \)
Next, we substitute these \( x \) values back into one of the original equations to find the corresponding \( y \) values. Using \( y = 5x - 7 \):
For \( x_1 \):
\[
y_1 = 5\left(\frac{7 + \sqrt{61}}{6}\right) - 7 = \frac{35 + 5\sqrt{61}}{6} - 7 = \frac{35 + 5\sqrt{61} - 42}{6} = \frac{-7 + 5\sqrt{61}}{6}
\]
For \( x_2 \):
\[
y_2 = 5\left(\frac{7 - \sqrt{61}}{6}\right) - 7 = \frac{35 - 5\sqrt{61}}{6} - 7 = \frac{35 - 5\sqrt{61} - 42}{6} = \frac{-7 - 5\sqrt{61}}{6}
\]
Thus, the solutions to the system of equations are:
1. \( \left( \frac{7 + \sqrt{61}}{6}, \frac{-7 + 5\sqrt{61}}{6} \right) \)
2. \( \left( \frac{7 - \sqrt{61}}{6}, \frac{-7 - 5\sqrt{61}}{6} \right) \)
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution